A retrospective cohort study of super-refractory status epilepticus in a tertiary neuro-ICU setting. (February 2021) - Kerin, Bellami; Rajakulendran, Sanjeev; Kullmann, Dimitri M.; Neligan, Aidan; Walker, Matthew C.
Highlights: Duration of SRSE and time spent in the NHNN ICU has decreased over time. Mortality of SRSE is lower than previous studies and has not changed over time. Morbidity resulting from SRSE remains high with no change over time. Abstract: Purpose: Over the last decade, the range of treatments available for the management of super-refractory status epilepticus (SRSE) has expanded. However, it is unclear whether this has had an impact on its high mortality and morbidity. The aim of this study was to investigate whether there has been a change in the outcome of SRSE over time in a neurological intensive care unit (ICU) within a tertiary centre. Methods: Analysis of a retrospective cohort of 53 admissions from 45 patients to the neurological ICU at the National Hospital for Neurology and Neurosurgery, Queen Square, London, between January 2004 and September 2018. Results: Significant reductions were observed in both duration of SRSE over time and in the time spent in ICU, suggesting that treatment quality has improved over time. A median of four antiseizure drugs (ASDs) were given prior to seizure resolution. In 23 % resolution of SRSE occurred following optimisation of current treatment rather than introduction of a new ASD. The mortality rate was very low at 11 % by 6 months; however, there was no indication of improvement in outcome as all surviving patients had a modified Rankin scale score of 3−5 upon discharge from ICU, classified as moderate-to-severe disability. Conclusion: Neither the survival rate nor the outcome score changed significantly over time, suggesting that changes in the treatment of SRSE have had no impact on patient outcome.